Incubation lighting schedules and their interaction with matched or mismatched post hatch lighting schedules: Effects on broiler bone development and leg health at slaughter age. (October 2017) - van der Pol, Carla W.; van Roovert-Reijrink, Inge A.M.; Aalbers, Gerald; Kemp, Bas; van den Brand, Henry
Abstract: The incidence of leg pathologies in broiler chickens with a developmental origin may be decreased by stimulating embryonic bone development through lighting schedules during incubation, but this may depend on post hatch lighting conditions. Aim was to investigate how lighting schedules during incubation and their interactions with matched or mismatched lighting schedules post hatch affected bone development and leg health at slaughter age. In a 3 × 2 factorial designed experiment, eggs were incubated under continuous cool white LED light (Inc24L ), 16 h of light, 8 h of darkness (Inc16L:8D ), or continuous darkness (Inc24D ) from set till hatch. After hatch, broilers were housed under continuous light (PH24L, to match Inc24L and Inc24D ) or 16 h of light, 8 h of darkness (PH16L:8D, to match Inc16L:8D ). Gait scores were determined on D21, D28, and D34. After slaughter on D35, legs were scored for varus-valgus deformities, rotated tibia, tibial dyschondroplasia, bacterial chondronecrosis with osteomyelitis (BCO), epiphyseolysis, and epiphyseal plate abnormalities from 1 = absent to 4 = severe. Femur and tibia dimensions and mineral density were determined. Inc24L led to more epiphyseal plate abnormalities than Inc16L:8D or Inc24D . Inc24D led to more BCO than Inc16L:8D . Gait scores on D21, D28, and D34, and bone dimensions did not differ between treatments. Inc24L led to higher femur mineral density than Inc24D with Inc16L:8D intermediate. Providing a chicken with a matched post hatch lighting schedule did not affect most measurements of bone development and health. It can be concluded that a circadian incubation lighting schedule may improve leg health in broilers. Highlights: Incubating broiler chicken embryos under 16 h of light, followed by 8 h of darkness (Inc16L:8D) resulted in fewer epiphyseal plate abnormalities in the leg bones at slaughter age than incubation under continuous light (Inc24L) or continuous darkness (Inc24D). Incubating broiler chicken embryos under Inc16L:8D resulted in less bacterial osteomyelitis with chondronecrosis in the femur than incubation under Inc24D. Providing a chicken with a post hatch lighting schedule that matched the incubation lighting schedule did not greatly affect bone development and leg health.